Estudo sobre as diferenças de práticas contábeis nas demonstrações contábeis societárias e regulatórias de distribuidoras de energia elétrica no Brasil - Hoppe, Aderbal Alfonso (2012)
At the close of the financial statements at December 31, 2010, corporate accounting practices in Brazil underwent the largest transformation in their history, in aligning with international accounting standards. This process generated differences in accounting practices between those accepted under tax legislation and those accepted under economic sector regulatory environments. The electric power distribution sector, in providing a public service, is regulated by a Granting Authority. The two main methods of regulation and inspection used by the Granting Authority are: i) to establish tariff practices so that through this mechanism there is control over levels of revenue and costs; and ii) to establish accounting practices through the Electrical Sector Accounting Manual. Concession agreements are standardized with similar economic and financial characteristics, which in turn, generate similar accounting events. This work is intended to analyze the differences in accounting practices between corporate financial statements and regulatory financial statements. To achieve this objective a conceptual review of the corporate and regulatory accounting practices was performed, including the economic and financial characteristics of the main examples of these differences in accounting practices. It was concluded through analysis of corporate and regulatory balance sheets at December 31, 2011, that despite the fact that corporate and regulatory accounting practices are formalized and mandatory for the balance sheet at that base date, there were inconsistencies, or a lack of application, of the accounting practices required under regulatory accounting. Accordingly, while it is evidently a positive notion to prepare and disclose regulatory financial statements that reconcile with accounting practices, at this stage this requires more detail and supplementary information in regulatory financial statements, as well as the complete adoption of regulatory accounting practices by all electric power distributors